Halal Tech on the Wrist: Reviewing Alcohol Biosensors and the Emerging Concept of SenseHalal, a Smart Wearable for Halal Verification - Ningrum, Karina Primatyas (Proceeding International Conference on Religion, Science and Education, 2026)
In today’s innovation-driven world, halal assurance extends beyond ingredients—it has become a lifestyle expectation. The increasing diversity of beverages and pharmaceuticals has heightened concerns among Muslim consumers regarding hidden alcohol content. Studies show that ethanol is still widely used as a solvent or preservative, and current labeling systems often fail to clarify its source or concentration. As a result, there is a growing need for accessible, real-time tools to support halal verification, particularly for tech-oriented young Muslims and travelers. Recent research on alcohol biosensors offers promising solutions. Wearable and transdermal biosensors using alcohol oxidase (AOX) or alcohol dehydrogenase (ADH) enzymes have demonstrated high specificity and sensitivity for ethanol detection, with reported accuracy levels up to 90%. Electrochemical transducers now allow stable readings through sweat or skin vapor, as validated by several studies in Biosensors & Bioelectronics and IEEE Sensors Journal (2020–2024). Integration with IoT platforms, AI-based data interpretation, and cloud databases further enhances real-time connectivity and traceability, aligning well with modern halal assurance frameworks. Building upon these advancements, this review introduces the conceptual framework of SenseHalal—a smart wearable designed to merge biosensor precision with digital convenience. By combining verified scientific principles and user-centered design, SenseHalal envisions halal verification as an effortless daily habit. This concept embodies the essence of Halal Tech 5.0, where technology, faith, and innovation coexist—empowering individuals to uphold halal integrity literally at their fingertips, or in this case, on their wrist.